PENGEMBANGAN TES DIAGNOSTIK MENGGUNAKAN APLIKASI GOOGLE FORM MATERI MOMENTUM DAN IMPULS UNTUK SISWA SMA - Maulidiansyah, Deka; Maria S, Haratua Tiur; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to develop a diagnostic test with google form application used to explore students’ misconceptions on momentum and impulse in Senior High School. This study applies a research and development design (R & D). Diagnostic tests are developed based on the students' initial concepts on momentum and impulse which is taken from several previous studies from physics education department UNTAN. The population of this study was conducted at state senior high school students in Pontianak. The sample of this research were 97 students from grade XI. This study delivered 15 items diagnostic test question which is divided into two categories; moderate and easy. The moderate questions were 13 items while the easy numbered 2 items. The content validity level of this study was 0.70. Then, the reliability showed 0.715. The level of legibility categorized as can be used in senior high school (5.13). Based on validation result above with index Aiken 1 and some students’ response data, google form aplication can be categorized as the high category (87,6%). So, google form application can be used for diagnostic test question. This research also is expected can be used by teacher in detecting students’ misconception on momentum and impulse.. Keywords: Diagnostic Test, Google Form, Momentum, Impulse